In Vivo Optical Imaging of Myelination Events in a Myelin Basic Protein Promoter-Driven Luciferase Transgenic Mouse Model. (May 2018) - Cao, James; Hu, Yanping; Shazeeb, Mohammed Salman; Pedraza, Carlos E.; Pande, Nilesh; Weinstock, Daniel; Polites, Gregory H.; Zhang, Wenfei; Chandross, Karen J.; Ying, Xiaoyou
The compact myelin sheath is important for axonal function, and its loss can lead to neuronal cell death and irreversible functional deficits. Myelin is vulnerable to a variety of metabolic, toxic, and autoimmune insults. In diseases like multiple sclerosis, there is currently no therapy to stop myelin loss, underscoring the need for neuroprotective and remyelinating therapies. Noninvasive, robust techniques are also needed to confirm the effect of such therapies in animal models. This article describes the generation, characterization, and potential uses for a myelin basic protein-luciferase (MBP-luci) transgenic mouse model, in which the firefly luciferase reporter gene is selectively controlled by the MBP promoter. In vivo bioluminescence imaging can be used to visualize and quantify demyelination and remyelination at the transcriptional level, noninvasively, and in real time. Transgenic mice were assessed in the cuprizone-induced model of demyelination, and luciferase activity highly correlated with demyelination and remyelination events as confirmed by both magnetic resonance imaging and postmortem histological analysis. Furthermore, MBP-luci mice demonstrated enhanced luciferase signal and remyelination in the cuprizone model after treatment with a peroxisome proliferator activated receptor-delta selective agonist and quetiapine. Imaging sensitivity was further enhanced by using CycLuc 1, a luciferase substrate, which has greater blood–brain barrier penetration. We demonstrated the utility of MBP-luci model in tracking myelin changes in real time and supporting target and therapeutic validation efforts.